CURRENT STATE OF THE PROBLEM OF FORMATION CULTURES OF COMMUNICATION OF THE FUTURE TEACHERS BY DIALOGICAL MEANS LEARNING SITUATIONS - Lysevych, O.V. (Pedagogy of Higher and Secondary Education, 2004)
The article deals with the various problems and aspects of communicational culture formation in dialogue training studying situation of professional orientation.